PENERAPAN SMOOTHING B-SPLINES PADA HUBUNGAN ANTARA PERTUMBUHAN EKONOMI DAN TINGKAT KEBAHAGIAAN - Muhammad Fajar; Eko Fajariyanto (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2022)
This study aimed to model the smoothing of B-splines on the relationship between happiness and economic growth. The method used in this research is smoothing B-splines, which were in the process of determining knots and smoothing parameters (λ) based on the minimum GCV. The data used in the study came from Badan Pusat Statistik-Statistics Indonesia. The results of this study concluded that the smoothing of B-splines is quite good at modeling the relationship between the level of happiness (response variable) and economic growth (predictor variable). The smoothing B-splines model can explain the variation in the level of happiness by 71.583 percent.